Pendidikan Formal Era Hindia Belanda di Kepulauan Sangihe Pada tahun 1848 – 1945 - Veronika Horohiung (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2016)
This research is a historical with the problem’s focus in how the development of formal education at Sangihe Island in the end of era XIX century and early XX century. The purpose of this research to use in historic method. Spesifically for Sangihe Island the purpose of build and education institute by Netherland especially not for the impotance of Indonesian people in common but special for Sangihe people actually for the Indonesia people that is it fill low position in government and to fill the manpower of company so that in the future the programs of education in Indonesia will more important orientation of society. Not just political importence